ANALISIS PENERAPAN PERATURAN PEMERINTAH NOMOR 71 TAHUN 2010 PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN SANGGAU. - admin, ZAIN ISLAMI B41111091 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Standar Akuntansi Pemerintahan (SAP) is the standard rules regulating about the presentation of the government's financial statements. The standard is stated in the form of Pernyataan Standar Akuntansi Pemerintahan (PSAP) and is equipped with a Kerangka Konseptual Akuntansi Pemerintahan (KKAP). The financial statements are prepared to provide relevant information about the financial position and all transactions conducted by a reporting entity within a reporting period. This research is aimed to analyze the application of PP No. 71 in 2010 concerning Accounting Standards of Government for presentation of financial statements at Badan Pengelola Keuangan dan Aset Daerah (BPKAD) in the District Sanggau in fiscal year 2014, as well as the constraints is faced by BPKAD Sanggau in its application. The results of this study indicate that BPKAD Sanggau not yet fully apply the PP No. 71 in 2010 on the presentation of its financial statements because of many obstacles faced such a low level of quality of human resources managers, limited device support and lack of socialization by the government. Therefore, this research suggests that the necessary activitiesÂ  improve the quality of human resources managers, and socialization will be undertaken by the government. Keywords: Standar Akuntansi Pemerintahan (SAP), the financial statements, PSAP